Rapid construction of TiO2 aggregates using microwave assisted synthesis and its application for dye-sensitized solar cells. Issue 12 (11th February 2015) - Wang, Xuyang; Tian, Jianjun; Fei, Chengbin; Lv, Lili; Wang, Yajie; Cao, Guozhong
<x xml:space="preserve">Abstract</x> Hierarchical TiO2 nanocrystallite aggregates are obtained by microwave synthesis in a few minutes, and they show high light scattering and larger surface area as well as improve the performance of dye-sensitized solar cells.